PROCESSES OF FORMATION OF INTELLECTUAL ABILITIES OF PRESCHOOL CHILDREN BY MEANS OF INNOVATIVE TECHNOLOGIES - Altibaeva Gulbahor Majitovna (Scholar Express Journal, 2022)
The article discusses issues related to the attraction of information and communication technologies, as well as methods of active learning tools for the development of intellectual abilities of students
Keywords: Intelligence; information technology; means and methods of active learning; preschoolers